Myocardial Remission in High Burden Outflow Tract Premature Ventricular Complex-Induced Cardiomyopathy after Radiofrequency Catheter Ablation: Case Report - Mochamad Rizky Hendiperdana; Erika Maharani (Jurnal Kardiologi Indonesia, 2026)
Background: Premature Ventricular Complex (PVC)-induced Cardiomyopathy (PVC-CMP) is a spectrum of dilated cardiomyopathy. Case Illustration: A 51-year-old female patient who was diagnosed with high suspicion of PVC-CMP underwent successful 3D mapping radiofrequency catheter ablation with a good result. Post-ablation 24-hour ECG-Holter evaluation showed a significant reduction of PVC burden. Echocardiographic evaluation 5 months post-ablation showed improvement in left ventricular systolic function parameters. The presence of high-burden PVC with a typical outflow tract origin could raise suspicion of a specific PVC-CMP aetiology. PVC burden emerged as a major predictor of the development of CMP. Several criteria can be used to identify PVC-CMP. Our case met those descriptive criteria, increasing the likelihood of PVC-CMP. Conclusion: PVC-CMP should be considered in patients with dilated cardiomyopathy who are accompanied by frequent outflow tract origin PVC (> 10 % burden). Early recognition of PVC-CMP is essential, as removal of the primary aetiology improves ventricular structure and function.